Electron conduction mechanisms in magnetic tunnel junctions fabricated using amorphous Si-Zn-Sn-O as a low-resistive semiconducting barrier. (June 2023) - Saha, D.; Lee, Sang Yeol
Highlights: Direct-tunneling is observed in the low-voltage regime for all the fabricated devices. Experimental results in the direct tunneling regime are further verified by simulations. Extracted barrier height from simulation closely matched with the expected results of band-offset at the SZTO/CoFeB interface. Beyond direct tunnelling regime trap assisted Pool Frenkel emission is observed. Low value of tunneling magnetoresistance is attributed to various inelastic conduction channels. Abstract: CoFeB/ Si-Zn-Sn-O /CoFeB magnetic tunnel junctions (MTJs) have been fabricated using amorphous Si-Zn-Sn-O as a low-resistive semiconducting barrier. In the low bias voltage range (up to ∼0.2 V), direct tunneling is found to be the dominant transport mechanism in MTJs. Tunneling conduction is further verified by simulation of tunnel current density and differential conductance using Simmon's and Brinkmann model, respectively. Simulated results provided valuable insights into the barrier properties, including interfacial barrier height, thickness, and barrier asymmetry. Above the direct tunneling regime, electron transport in MTJs is governed by Pool Frenkel emission, which possibly arises due to the presence of high-density localized tail states below the conduction band of amorphous Si-Zn-Sn-O. Tunnelling magnetoresistance value of MTJs is found to be very low, which is attributed to the presence of various inelastic conduction channels. The results of this study might be useful to explore the potential of amorphous Si-Zn-Sn-O for fabricating low-resistive MTJ based spintronic devices.